COMPARATION OF LEARNING OUTCOMES BETWEEN USING of PBL MODELS and TAI MODELS JUDGING FROM STUDENTS MOTIVATION - Dwi Oktaviani Ogara (Sosio-Didaktika: Social Science Education Journal, 2019)
This was a quasi-experimental research study employing the factorial 2x2 design and varian analyzes (anava) used as a data analysis technique. The results of the research show that: (1) there are significant differences in learning outcomes between student’s learning by using PBL model and student’s who learn to use TAI model. Shown with the average value of the final learning outcomes of student's who study with PBL model is 18.81 while with the TAI model is 11.70, (2) there are significant diffrences in  learning outcome between the use of PBL model and TAI model at learners who have high learning motivation. Shown with the average value of learning outcomes of student's who study with PBL model is 23.00 while with the TAI model is 11.75, (3) there are  significant differences of the  learning outcome between the use of PBL model and TAI model at learners who have low learning motivation. Shown with the average value of learning outcomes of student's who study with PBL model is 6.83 while with the TAI model is 12.42 (4) there is significant interaction effect between of learning models and student’s motivation to learning outcomes of economic. Shown from the results of the two-way ANOVA test obtained a significance value of 0.047 where the value is smaller than the significance level of 0.05. Keywords:PBL, TAI, learning motivation and learning outcome